Perhitungan Umur Sisa Perkerasan Lentur Berdasarkan Analisis Data Lalu Lintas pada Ruas Jalan Drs. Esau Sesa, Manokwari, Papua Barat: Perhitungan Umur Sisa Perkerasan Lentur Berdasarkan Analisis Data Lalu Lintas pada Ruas Jalan Drs. Esau Sesa, Manokwari, Papua Barat - Winda Sary de Queljoe; Made Budi Purnama Putra; Tegar Adi Nata (Universitas Papua, 2025)
Roads are vital infrastucture that support the social, economic, and logistical activities of a region. Over time, pavement performance decreases due to repeated traffic loads, environmental conditions, and constuction quality variations. This study aims to analyze the remaining service life of flexible pavement based on traffic data on Drs. Esau Sesa Road, Manokwari Regency, West Papua Province. Traffic data were collected through a seven days survey in December 2024 and processed using the Indonesia Highway Capacity Manual (PKJI, 2023) and the Road Pavement Design Manual (MDPJ, 2024). Equivalent single axle load (ESAL) and cumulative ESAL (CESAL) calculations were conducted for a 20 years projection period (2024-2044). The analysis result indicateed for a CESAL value of 2,393,429 ESAL with an initial remaining service live (RSL) of 98,91% in 2025, decreasing to 21,84% with a CESAL of 186,079,039 ESAL in 2044. Based on the AASHTO (1993) classification, the pavement condition requires routine maintenance until 2038, overlay between 2039-2043, and rehabilitation in 2044.